2014
DOI: 10.1371/journal.pone.0113257
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Vitamins C and E on p,p′-DDT-Induced Cytotoxicity via the ROS-Mediated Mitochondrial Pathway and NF-κB/FasL Pathway

Abstract: Dichlorodiphenoxytrichloroethane (DDT) is a known persistent organic pollutant and liver damage toxicant. However, there has been little emphasis on the mechanism underlying liver damage toxicity of DDT and the relevant effective inhibitors. Hence, the present study was conducted to explore the protective effects of vitamin C (VC) and vitamin E (VE) on the cytotoxicity of DDT in HL-7702 cells and elaborate the specific molecular mechanisms. The results demonstrated that p,p′-DDT exposure at over 10 µM depleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Mitochondrial membrane potential (Δψm) was analyzed in 16HBE cells, according to the manufacturer's protocol for a commercial kit (KeyGEN BioTECH, Nanjing, China). The details were as described for our previous methods (Jin et al, 2014b).…”
Section: Mitochondrial Membrane Potential (δψM) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial membrane potential (Δψm) was analyzed in 16HBE cells, according to the manufacturer's protocol for a commercial kit (KeyGEN BioTECH, Nanjing, China). The details were as described for our previous methods (Jin et al, 2014b).…”
Section: Mitochondrial Membrane Potential (δψM) Assaymentioning
confidence: 99%
“…Generation of ROS was determined by fluorometric analysis, using 2,7-dichlorofluorescin diacetate (DCFH-DA), which was obtained from Beyotime Institute of Biotechnology (Nan tong, China) as described for our previous methods (Jin et al, 2014b).…”
Section: Determination Of Ros Generationmentioning
confidence: 99%
“…Measurement mitochondrial membrane potential (Djm) was performed in 16HBE cells, according to the manufacturer's protocol for a commercial kit (KeyGEN BioTECH, Nanjing, China). The detail was described by our previous method (Jin et al, 2014b). Briefly, for fluorometric analysis, cells were incubated with 1.0 mg mL À1 JC-1 for 15 min at 37 C, collected and placed in a 96-well plate to assess cell fluorescence intensity.…”
Section: Mitochondrial Membrane Potential (Djm) Assaymentioning
confidence: 99%
“…Previous studies reported beneficial effects of omega‐3 fatty acids and AA on enhancing cell viability in different cell types after exposure to a wide range of stress‐induced stimuli . However, increasing evidence indicated that two or more antioxidants could exert synergistic effects.…”
Section: Discussionmentioning
confidence: 99%